2016
DOI: 10.1371/journal.pone.0147290
|View full text |Cite
|
Sign up to set email alerts
|

The Species and Origin of Shark Fins in Taiwan’s Fishing Ports, Markets, and Customs Detention: A DNA Barcoding Analysis

Abstract: The increasing consumption of shark products, along with the shark’s fishing vulnerabilities, has led to the decrease in certain shark populations. In this study we used a DNA barcoding method to identify the species of shark landings at fishing ports, shark fin products in retail stores, and shark fins detained by Taiwan customs. In total we identified 23, 24, and 14 species from 231 fishing landings, 316 fin products, and 113 detained shark fins, respectively. All the three sample sources were dominated by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 30 publications
0
37
0
4
Order By: Relevance
“…Their contributions ranged from 34.1-64.2% (blue) to 0.2-1.2% (bull and shortfin mako). Skewed species composition is concordant with fin exports from Indonesia, United Arab Emirates, and Taiwan, which are important suppliers of HK, albeit each with its own unique set of dominant species (Jabado et al 2015;Sembiring et al 2015;Chuang et al 2016). It is also concordant with the 1999-2001 HK trade (Clarke et al 2006a(Clarke et al , 2006b.…”
Section: Species Compositionmentioning
confidence: 77%
“…Their contributions ranged from 34.1-64.2% (blue) to 0.2-1.2% (bull and shortfin mako). Skewed species composition is concordant with fin exports from Indonesia, United Arab Emirates, and Taiwan, which are important suppliers of HK, albeit each with its own unique set of dominant species (Jabado et al 2015;Sembiring et al 2015;Chuang et al 2016). It is also concordant with the 1999-2001 HK trade (Clarke et al 2006a(Clarke et al , 2006b.…”
Section: Species Compositionmentioning
confidence: 77%
“…Red letters/numbers and shark symbols depict CoP16 listed species (took effect late 2014), yellow letters/numbers and shark symbols depict CoP17 listed species (took effect October 2017) species to Hong Kong (Figure 1). Many exporting nations previously known to land these species were not among those to report trade, again, suggesting low compliance with CITES reporting requirements in 2015-2016 (Chuang, Hung, Chang, Huang, & Shiao, 2016b, 2016aJabado et al, 2015;Sembiring et al, 2015). Relatively low compliance with CITES regulations, especially in the initial phase of implementation, is documented in other taxa including seahorses (Foster, Wiswedel, & Vincent, 2014), tigers, rhinoceros (Cheung, 1995), and turtles (Rehman, Jafar, Ashraf Raja, & Mahar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys in Hong Kong in 1999–2001 (Clarke, Magnussen, Abercrombie, McAllister, & Shivji, ), 2014–2015 (Fields et al., ), and a few of their top trading partners (Chuang, et al. ; Jabado et al., ; Sembiring et al., ) all showed that fins of several species listed at CoP16 were commonly traded prior the listings taking effect. The first objective of the present study was to assess the global position of Hong Kong as legal importer of fins from CITES listed species according to CITES trade records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other provincial jurisdictions thresher sharks are commercially targeted for their meat and valuable fins that are exported to various markets across Asia (Liu et al, 2013;Chuang et al, 2016). Since fisheries legislation is mandated at the provincial level in the Philippines, it would be necessary to reconcile the differences of at least five territorial governments, and all of the municipalities that have fisheries interests therein (Simpfendorfer et al, 2011;Dulvy et al, 2017), to develop and effect conservation policy for the thresher sharks that use Monad Shoal as their philopatric homing destination (Jorgesen et al, 2009;Dulvy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%